DIETETIC EVALUATION IN ATHLETES OF DIFFERENT SPORTS MODALITIES (Fiep Bulletin - online, 2014)
The aim of this study was to assess the consumption of calories, macronutrients (carbohydrates, protein and fat ) of athletes in different sports modalities. Methods: A nutritional evaluation was done to verify stature, weight and eating habits of 40 athletes, 10 footballers, 15 swimmers (7 men, 8 women) and 15 volleyball players, participants in the project “Nutrição Desportiva” by Feevale in the city of Novo Hamburgo, Rio Grande do Sul, Brazil. For measuring weight a Filizola TM scale with accuracy up to 100 gram was used and for measuring height a stadiometer Gofeca TM, with accuracy of up to milimeters(mm), fixed on a wall, without baseboard. The athletes were barefoot and wearing a minimum of clothes. Afterwards, food intake was assessed. As a final stage an indiviual interview took place, the “24h recall inquiry” (R24), and after that athletes were given a “food control table” where they registered their daily consumption of food and their respective amounts for seven days. Food consumption was analyzed by means of the software “DietWin Clínico 3.0” and compared to recommendation proposed by Sociedade Brasileira de Medicina do Esporte (SBME). After data were processed, they were treated through descriptive analysis (SPSS 12.0) for determination of means, standard deviations and percentages. Results suggest that the calories consumption was lower than the recommended in all modalities. 75% of the female swimmers did not reach the energy recommendation; 43% of the male swimmers and 40% of the soccer players consume protein quantities above nutritional recommendation; from 20 to 29% of the athletes of all modalities consume lipid above nutritional recommendation. We conclude that most athletes should increase their energy intake and adequate the macronutrients proportion.
Keywords: energy consumption; sport; macronutrients